WATER RESOURCES IN THE WIDER AREA OF THE APOSELEMIS BASIN, CRETE ISLAND, GREECE - Voudouris, K.; Alexopoulos, A.; Antonakos, A.; Kallergis, G. (Bulletin of the Geological Society of Greece, 2007)
The estimation of hydrologie balance is useful in order to assess the safe yield of the aquifer systems and therefore to establish their rational exploitation and sustainable management. Over-abstractions of groundwater in Aposelemis basin resulted in a severe disequilibrium of its water balance. In order to overcome this disequilibrium we studied the hydrological balance in the wider area ofDikti mountain which comprises the drainage basins of Aposelemis river, ofLasithi and Katharo plateaus and of the rest of the drainage area of Dikti. The data used are the monthly values of Aposelemis runoff in the gauge station at Potamies and rainfall data for the period 1967-2003 from seven stations located within or in the close vicinity of the drainage basin of Aposelemis. Using ArcView GIS, the hydrological basin of Aposelemis river and the drainage area ofDikti were delineated, based on the digital elevation model (DEM). The actual évapotranspiration was estimated by the Thornthwaite method. A high inter-relationship exists between the flow of the Aposelemis river and rainfall outside the conventional boundaries of the Aposelemis basin. A significant portion of the annual rainfall, in that wider area is not only recharging the karst systems downstream but also contributing to the flow of Aposelemis river. Karst aquifer systems are partially drained by large coastal and submarine brackish springs and by inland freshwater springs. Finally, tracer studies carried out by IGME confirmed the hydraulic connection between Lasithiplateau and downstream aquifer systems.